Investigation of the effect of carbonization temperature of plant biomass on the electrochemical properties of carbon material - Ivanichok, N.Ya.; Ivanichok, O.M.; Budzulyak, I.M.; Kolkovskyi , P.I.; Rachiy , B.I.; Vyshnevskyi , O.A.; Borchuk , D.S.; Ivaniv, I.I.; Soltys, A.M. (Physics and Chemistry of Solid State, 2024)
Porous carbon materials (PСM) with different pore distributions in size and size of the specific surface area up to 250 m2/g were obtained by changing the carbonization temperature of plant biomass, namely walnut shells. The electrodes of electrochemical supercapacitors are formed based on the obtained carbon materials. The electrochemical behavior of PCM in 33% aqueous KOH solution has been studied by cyclic voltammetry and galvanostatic discharge-discharge methods and the value of their specific capacitance. The physicochemical processes occurring at the carbon electrode/electrolyte interface have been investigated by the method of impedance spectroscopy.